Dispositivo De Apoyo De Fuerza Lumbar Para La Manipulación Manual De Laminas En El Proceso De Fabricación De Cajas De Carton Corrugado. (2025)
Injuries caused by poor posture, incorrect procedures when handling loads, sudden movements, or simply not knowing the regulations for carrying out physical work within a company expose many workers to injuries that can severely affect the permanent integrity of the individual. A survey is conducted in a specific company in the corrugated cardboard manufacturing sector, highlighting the postures, performance, and conditions that different employees must undergo in various activities every day.